2003
DOI: 10.1191/1352458503ms948oa
|View full text |Cite
|
Sign up to set email alerts
|

Interferon beta in relapsing-remitting multiple sclerosis: an independent postmarketing study in southern Italy

Abstract: This independent, population-based surveillance study monitored the efficacy and safety of interferon beta (IFNbeta) products in 1033 patients with relapsing-remitting multiple sclerosis (RRMS) from 15 centres in Italy. Relapses, Expanded Disability Status Scale (EDSS) scores, and adverse events were evaluated for up to 24 months. Data of patients with a baseline EDSS score < or = 3.5 are reported. The proportions of relapse-free patients were similar among the groups at 12 and 24 months (P = 0.10). IFNbeta pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 13 publications
6
45
1
1
Order By: Relevance
“…These results are in line with other short- and long-term real-world postmarketing studies [11,12,13,14,15,16,17,18,19,20,21]. Nevertheless, 2 previous head-to-head trials, EVIDENCE [9] and INCOMIN [10], showed superior efficacy for SC IFNβ compared with IM IFNβ in terms of time to the first clinical MS relapse on study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These results are in line with other short- and long-term real-world postmarketing studies [11,12,13,14,15,16,17,18,19,20,21]. Nevertheless, 2 previous head-to-head trials, EVIDENCE [9] and INCOMIN [10], showed superior efficacy for SC IFNβ compared with IM IFNβ in terms of time to the first clinical MS relapse on study.…”
Section: Discussionsupporting
confidence: 73%
“…Benson and Hartz [26] reported that the estimates of treatment effects from observational studies and randomized controlled trials are similar. The value of observational studies should therefore not be underestimated since phase 4 studies and retrospective chart reviews can also reveal important differences among drugs in the same class that were not detected in controlled phase 2 or 3 clinical trials [17]. In addition, in Switzerland all DMTs are approved first-line treatments for MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, over a follow-up period ranging from 2 to 4 years, the proportion of patients switching is between 3 and 13% [5, 8, 10, 11, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Three randomized double-blind placebo-controlled multicentric studies have shown that IFN-␤ reduces the relapse rate by about 30% [1][2][3] and slows the progression of disability in patients with RRMS. Several studies have suggested that the 3 IFN-␤ types available are equally efficacious [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%